Perancangan user interface pada game edukasi bahasa arab menggunakan metode design thinking - Fajri Fahreza Azeta; Nazruddin Safaat H; Muhammad Irsyad; Febi Yanto (Universitas Muhammadiyah Riau, 2023)
Technology is developing rapidly, providing convenient access to information, and sparking interest in technological developments. The growth of technology influences children's learning. The integration of technology creates new and exciting learning experiences, especially in early childhood education. The use of smartphones as innovative learning media offers interactivity and attraction. In game development, attention to the User Interface (UI) is crucial to ensure a suitable gaming experience that supports the overall game experience. The research methodology used in conducting this research is the